RELATIONSHIP OF INFECTION AND GAMMA INTERFERON ( IFN ) OF PLASMA AND LYMPHOCYTE CULTURE SUPERNATANT IN IRON DEFICIENCY ANEMIA PATIENTS WITH INFECTION - Suega, Ketut; Bakta, I Made (journal of internal medicine, 2009)
Iron is an essential nutrient for every living cells because of it role as molecule for transport of oxygen, as well as DNAsynthesis through synthesis of ribonucleotide reductase. Although the underlying mechanism of immune defect in iron deÞ ciencyanemia (IDA) is not clearly understood, multifactor events considered play their contributing roles such as impairment of T-cellproliferation and activities, altered cytokine production of Interleukin-2 (IL-2) and Interferon gamma (IFN ).Cross sectional study was done to asses the relationship of gamma IFN with infection in IDA patients on plasma andlymphocyte culture supernatant of IDA patients. Sixty-four IDA patients treated in Sanglah General Teaching Hospital wererecruited, and 31 (48.4%) out of 64 IDA patients were man and 33 (51.6%) women, have been selected for the study. This studyfound 17 (26.7%) IDA patients with infection, aged 38 ± 14.48 years and 47 (73.3%) IDA patients without infection, with ageaverage of 40.5 ± 14.4 years. The study revealed that there were no differences of cytokine level observed between older andyounger age (upper and below 44.5 years) in IDA patients. Furthermore, no differences of cytokine level were found based ongender between IDA male 10.9 pg/l (8.60 ! 12.65) patients and IDA female patients 10.6 pg/l (7.50 ! 13.43) with Z -0.490,p = 0.624. Nevertheless, signiÞ cant differences were noted between plasma and supernatant of IFN in IDA patients withinfection when compared to IDA patients without infection (Z = - 2.638, p = 0.008 for plasma IFN ; and Z = -2.569, p = 0.010for supernatant IFN ).The study conclusion is that level of IFN from plasma and lymphocyte culture supernatant of patient suffered from IDAwith infection is signiÞ cantly lower when compared to IDA patient without infection